2013
DOI: 10.1164/rccm.201206-1028oc
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Attenuates Hypoxia-induced Pulmonary Arterial Hypertension Pathology via Reduction in 5-Hydroxytryptamine through Inhibition of Tryptophan Hydroxylase 1 Expression

Abstract: We report a novel mode of action for imatinib, demonstrating TPH1 down-regulation via inhibition of PDGFR-β signaling. Our data reveal interplay between PDGF and 5-HT pathways within PAH, demonstrating TPH1-dependent imatinib efficacy in collagen-mediated mechanisms of fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 51 publications
3
45
0
Order By: Relevance
“…Improvements in these areas would provide a tool by which more direct assessment of efficacy upon 5-HT-mediated complex remodeling diseases of the periphery could be made – an example of which could be the rodent hypoxia/SUGEN model of PAH which demonstrates increased TPH1 expression and 5-HT production, and is also sensitive to pCPA inhibition (Ciuclan et al, 2013; Thomas et al, 2013). Increased pulmonary artery endothelial cell (PAEC) TPH1 expression in PAH patients together with increased SERT expression in pulmonary artery smooth muscle cells (PASMC), may induce the hyperplasia central to PAH (Eddahibi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in these areas would provide a tool by which more direct assessment of efficacy upon 5-HT-mediated complex remodeling diseases of the periphery could be made – an example of which could be the rodent hypoxia/SUGEN model of PAH which demonstrates increased TPH1 expression and 5-HT production, and is also sensitive to pCPA inhibition (Ciuclan et al, 2013; Thomas et al, 2013). Increased pulmonary artery endothelial cell (PAEC) TPH1 expression in PAH patients together with increased SERT expression in pulmonary artery smooth muscle cells (PASMC), may induce the hyperplasia central to PAH (Eddahibi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As a novel approach to PAH, PDGF inhibitors have received attention (4,10,23). However, toxicities of PDGF inhibitors and heterogeneous actions of the agents are obstacles in their translation to clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis of PAH still remains poor (9,31). Several recent studies using animal models of PAH have indicated that proliferation of vascular cells and their escape from apoptosis are therapeutic targets, and that inhibition of the platelet-derived growth factor (PDGF) receptor may prevent and reverse PAH (4,11,23). However, current inhibitors of growth factor receptors are, in general, not highly specific and have different efficacies and serious side effects, which make the inhibitors unsuitable for clinical application.…”
mentioning
confidence: 99%
“…1,20 Wu et al 21 examined PDGFR signaling in genetically defined mouse embryonic fibroblasts (MEFs). The MEFs were engineered to express only PDGFRα or PDGFRβ, both, or neither.…”
Section: Discussionmentioning
confidence: 99%